Properties of high permeable concrete utilizing pozzolanic materials - Mohammed, B.S. (Asian Research Publishing Network, 2016)
To investigate the possibility of using pozzolanic materials in producing high permeable concrete (HPC), five materials were used to partially replacement to Ordinary cement: Silica fume, fly ash, paper mill ash, palm oil ash and rice husk ash. Several tests were conducted on the cementitious paste and also on the HPC. Results revealed that 5 of pozzolanic material replacement to Ordinary cement would yield the best results. However, the good performance of HPC can be determined through balancing the several characteristics such as compressive strength, void ratio, permeability, skid resistance and infiltration rate. Â© 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.